Pengaruh Return On Assets (ROA) dan Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan LQ45 Sub Sector Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2024 - Ashiva, Devitri Salsa; Prasetya, Bangun Putra (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the effect of Return on Assets (ROA) and Return on Equity (ROE) on stock prices in food and beverage sub-sector companies that are members of the LQ45 index and listed on the Indonesia Stock Exchange (IDX) during the 2019-2024 period. The method used in this research is a quantitative method with a descriptive approach. The data used is secondary data obtained through the annual financial statements of related companies and official IDX publications. The sampling technique was carried out by purposive sampling method, and the analysis used was multiple linear regression, F test, t test, and coefficient of determination (R²) with the help of SPSS 27. The results showed that simultaneously Return On Assets (ROA) and Return On Equity (ROE) had a significant effect on stock prices. Partially, the Return On Assets (ROA) and Return On Equity (ROE) variables have a positive and significant effect on stock prices, with an Fcount value of 4,355 with a coefficient of determination (Adjusted R²) of 0.521. This means that 52.1% of stock prices are influenced by Return On Assets (ROA), Return On Equity (ROE) while the remaining 47.9% is influenced by other factors outside this study.